2022
DOI: 10.1038/s41598-022-15415-z
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of endogenous and exogenous indole-3-acetic acid on atrazine stressed paddy field cyanobacterial biofertilizer Cylindrospermum stagnale

Abstract: Across the world, paddy fields naturally harbour cyanobacteria that function as biofertilizers and secrete various compounds like Indole-3-acetic acid (IAA) that help organisms in regulating their growth. Also, paddy field farming utilizes large amounts of pesticides (e.g. atrazine); but their continued application in the agricultural field causes toxicity in non-target cyanobacterial species that hinder their performance as a biofertilizer. Hence, the current study is an attempt to ameliorate the atrazine str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Previously, it has been reported that among many compounds that cyanobacteria produce, IAA promotes growth and prevents organisms from environmental stress such as desiccation, osmotic, cold shock, and heat shock. Further, IAA activates the antioxidant activity in the cell by inducing the expression of antioxidant enzymes such as CAT, SOD, and peroxidase [45]. A similar results have also been obtained in the present study which corroborates with the cited literature.…”
Section: Effect Of Temperature On Iaa Productionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previously, it has been reported that among many compounds that cyanobacteria produce, IAA promotes growth and prevents organisms from environmental stress such as desiccation, osmotic, cold shock, and heat shock. Further, IAA activates the antioxidant activity in the cell by inducing the expression of antioxidant enzymes such as CAT, SOD, and peroxidase [45]. A similar results have also been obtained in the present study which corroborates with the cited literature.…”
Section: Effect Of Temperature On Iaa Productionsupporting
confidence: 93%
“…IAA isolated from yeast has been known to inhibit the growth of weeds and therefore can be used as a herbicide and replace the chemical herbicides [48]. Similarly, it has been observed that usage of IAA or cyanobacterial biofertilizer ameliorates the atrazine toxicity in paddy crops [45]. Role of cyanobacteria as biofertilizers and soil stabilizers in agriculture has been well proved where it promotes cell division and plant elongation [49].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cyanobacteria can produce IAA, which promotes growth under normal conditions and provides protection against various stressors [ 33 ]. Studies that have examined the growth yield after adding exogenous IAA in quantities critical for hormone production have long established the fact that IAA aids cyanobacteria in growing [ 34 ].…”
Section: Introductionmentioning
confidence: 99%